1962
DOI: 10.1161/01.res.10.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the Bronchial Veins in a Heart-Lung-Bronchial Preparation

Abstract: Blood collected from the bronchial veins of a heart-lung-bronchial preparation consists of two components: (a) fraction from the bronchial arteries, and (b) pulmonary to bronchial shunt It is estimated that the latter is more than half of total bronchial venous flow. The pulmonary to bronchial shunt is reduced by procedures which increase pulmonary arterial pressure. An intrinsic nervous reflex mechanism is suggested to explain such a response, particularly because the bronchial veins are more sensitive than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

1962
1962
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 7 publications
2
13
1
Order By: Relevance
“…However, the present data do not agree with the results obtained by Martinez et al (1961) and Aramendia et al (1962), who reported that histamine caused dilatation and 5-HT caused a biphasic effect in the bronchial artery of the dog in vivo.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the present data do not agree with the results obtained by Martinez et al (1961) and Aramendia et al (1962), who reported that histamine caused dilatation and 5-HT caused a biphasic effect in the bronchial artery of the dog in vivo.…”
Section: Discussioncontrasting
confidence: 99%
“…Some actions of many of these mediators on various bovine blood vessels, including the pulmonary vasculature, have been described previously (Eyre, 1971;Burka & Eyre, 1974a;1977;Holroyde & Eyre, 1975 Aviado, 1962). It appears from the literature, that a bronchial vessel has never previously been studied in vitro, probably because the vessel, being very small, is difficult or impossible to obtain from the usual laboratory animal species.…”
Section: Introductionmentioning
confidence: 77%
“…The major hemodynamic and neural determinants of bronchopulmonary flow have been studied by several groups over the past four decades. The majority of investigators (3)(4)(5)(6)(7)(8)(9) have found that systemic arterial pressure, independent of cardiac output, is one of the principal factors determining bronchopulmonary shunt flow. Although the exact anatomic location of the connections between the bronchial and pulmonary circulations is a subject of some controversy (10, 1 1), all agree that the pulmonary arterial and venous pressures, reflecting the "outflow pressure" ofthe bronchopulmonary anastomoses, are also principal determinants.…”
Section: Introductionmentioning
confidence: 99%
“…Changes of flow in the diminutive precapillary anastomoses between the bronchial and the pulmonary vascular network are most unlikely to cause the initial rise of pressure in the pulmonary artery. Furthermore the results of the elegant animal experiments by Martinez et al (1961) and Aramendia, de Letona, and Aviado (1962) suggested that the flow from the pulmonary artery into the bronchial veins via anastomotic channels was not reduced by norepinephrine. Finally, whether an increase of blood flow could have been the cause of the early rise of pulmonary arterial pressure should be examined.…”
Section: Discussionmentioning
confidence: 99%